Cystatin A promotes the antitumor activity of T helper type 1 cells and dendritic cells in murine models of pancreatic cancer - Alessandro Nasti; Shingo Inagaki; Tuyen Thuy Bich Ho; Akihiro Seki; Keiko Yoshida; Kosuke Satomura; Yoshio Sakai; Shuichi Kaneko; Taro Yamashita (Molecular Oncology)
Pancreatic ductal adenocarcinoma (PDAC) is a disease with poor prognosis due to diagnostic and therapeutic limitations. We previously identified cystatin A (CSTA) as a PDAC biomarker and have conducted the present study to investigate the antitumor effects of CSTA. PDAC murine models were established with genetically modified PAN02 tumor cell lines to evaluate the antitumor immune response. PDAC mouse survival was significantly longer with CSTA, and its antitumor effect was mediated mainly by CD4+ cells and partly by CD8+ cells. We also observed an increased infiltration of CD4+ and CD8+ cells in tumors of mice overexpressing CSTA. Phenotypically, we confirmed higher T helper type 1 (Th1) cell activity and increased frequency and activity of M1 macrophages and dendritic cells (DCs) in CSTA‐overexpressing mice. Gene expression analysis highlighted pathways related to interferon gamma (IFN‐γ) induction and Th1 lymphocyte activation that were induced by CSTA. Macrophages and DCs shifted toward proinflammatory antitumor phenotypes. Furthermore, activated splenocytes of PDAC model mice expressing CSTA had increased proapoptotic activity. CSTA also promoted the selective migration of CD4+ and CD11c+ immune cells in an in vitro migration assay. In conclusion, CSTA exerts antitumor effects by enhancing Th1‐mediated antitumor effects through promotion of DC and M1 macrophage activity, thereby increasing immune cell chemotaxis. CSTA could be a novel therapeutic candidate for PDAC.